Analisa Koefisien Biaya Pekerjaan Pembesihan Dan Cetakan Beton Sesuai Penerapan Rencana Anggaran Pelaksanaan - Sutirto, Sutirto (Fakultas Teknik, Universitas Brawijaya, 2013)
Reinforced concrete unit price is influenced by the weight of steel reinforcement and concrete molds. Consumption coefficient factor 1 m3 concrete steel reinforcement seen from the use of reinforcement factor corresponding coefficient analysis list Bakhtiar Ibrahim, 1996 and Burgerlijke Open bare Werken (BOW), J. A. Muko - Muko, 1995, which is tied as the denominator vareabel weighing 110 kg/m3. Calculation results 1 m3 of concrete iron needs by operation as the numerator, that will get the value of the index coefficient analysis for concrete work. From the results koefiseien index value multiplied by all the coefficients contained in the analytical use of reinforcement or BOW Bakhtiar. This result will be a factor coefficients are used as the basis for calculation of unit price analysis used iron as needed according to the picture implementationKeywords : variable, use of reinforcement, formwork, the value of the coefficient